A study on the prevalence of thinness and obesity in school going adolescent girls of Kashmir Valley - Ali, Darakshan; Shah, Rohul Jabeen; Fazili, Anjum Bashir; Rafiq, M. M.; Mushtaq, Beenish; Iqbal, Qazi Mohammad; Dar, Sameena Yousuf (International Journal Of Community Medicine And Public Health, 2016)
Background: A vast majority of girls in India are suffering from either general or specific morbidities. Under nutrition and obesity are important nutritional problems in adolescents. In Indian adolescents the prevalence of under nutrition is 53.1% in males and 39.5% in females. In India the prevalence of obesity is also increasing with 8.3% in adolescent boys and 5.5% in adolescent girls. This is especially seen in the urban affluent class because of unhealthy eating, consumption of junk and fast foods and also due to changing lifestyles and physical inactivity. Adolescent girls constitute a socially disadvantageous group in our society. Methods: A cross sectional study design was adopted and the study was conducted in randomly selected schools in three districts of Kashmir Valley during April 2014 to March 2015. A total of 428 girls in the age group of 12 to 18 years were included in the study. Data was collected using a pre-tested and pre-structured proforma which included assessment of the dietary habits, anthropometric measurements and general physical examination of the study participants. Results: The prevalence of thinness in the study population was 35.70% and was significantly associated with SES, mother’s literacy and mother’s occupation (p value <0.001,0.039 and <0.001 respectively).The prevalence of overweight was 7.20% .It was observed that age, SES and residence had a significant association with the prevalence of overweight (p value 0.010, <0.001 and 0.001 respectively). The prevalence of overweight by WHR was 4.40% and that of obesity was 3.30%. Conclusions: Thus it is concluded from this study that a considerable proportion of adolescent girls suffered from thinness and obesity. We recommend that requisite measures be taken to address these concerns as this group constitutes a sizeable proportion of the Indian mothers of our future generation and their well-being is critically important for improving the nutritional health of women of the nation.